Cross-sectional survey of the Mental health and Addictions effects, Service impacts and Care needs of children, youth and families during the COVID-19 pandemic: the COVID-19 MASC study protocol. Issue 10 (26th October 2022) - Markoulakis, Roula; Khalid, Maida; Da Silva, Andreina; Kodeeswaran, Sugy; Sinyor, Mark; Cheung, Amy; Redelmeier, Donald; MacKillop, James; Scarpitti, Michael; Laird, Hannah; Foot, Jeanne; Levitt, Anthony
Abstract : Introduction: The COVID-19 pandemic has had a tremendous negative effect on the mental health and well-being of Canadians. These mental health challenges are especially acute among vulnerable Canadian populations. People living in Canada's most populous province, Ontario, have spent prolonged time in lockdown and under public health measures and there is a gap in our understanding of how this has impacted the mental health system. This protocol describes the Mental health and Addictions Service and Care Study that will use a repeated cross-sectional design to examine the effects, impacts, and needs of Ontario adults during the COVID-19 pandemic. Methods and analysis: A cross-sectional survey of Ontario adults 18 years or older, representative of the provincial population based on age, gender and location was conducted using Delvinia's AskingCanadians panel from January to March 2022. Study sample was 2500 in phases 1 and 2, and 5000 in phase 3. The Alcohol, Smoking and Substance Involvement Screening Test and Diagnostic Statistical Manual-5 Self-Rated Level 1 Cross-Cutting Symptom Measure-Adult were used to assess for substance and mental health concerns. Participants were asked about mental health and addiction service-seeking and/or accessing prior to and during the pandemic. Analyses to be conducted include: predictors of service access (ie, sociodemographics, mental illness and/or addiction, and social supports) before and during the pandemic, and χ 2 tests and logistic regressions to analyse for significant associations between variables and within subgroups. Ethics and dissemination: Ethics approval was obtained from the Sunnybrook Research Ethics Board. Dissemination plans include scientific publications and conferences, and online products for stakeholders and the general public.